ANALISIS YURIDIS ATAS PUTUSAN NOMOR: 014/Pdt.P/2014/PA-LPK TENTANG PENETAPAN AHLI WARIS DZAWIL ARHAM YANG MENDAPATKAN SELURUH HARTA WARISAN SI PEWARIS - TAUFIQ TAHIR YUSUF LUBIS (PREMISE LAW JURNAL, 2016)
Dzawil Arham in the Compilation of the Islamic Law is not included in the category of an heir because, according to the Compilation of the Islamic Law, there are three categories of heir: dzul fardin (dzawil furudh), asahabah, and substituting heir (Plasverfulling), while in the verdict No. 014/Pdt.P/2014/PA-LPK, the panel of judges in the hearing of the case appointed an heir that was not dzawil arham who had the right for the inheritance.   Keywords: Dzawil Arham, Heir, Court’s Verdict